1963
DOI: 10.1113/jphysiol.1963.sp007211
|View full text |Cite
|
Sign up to set email alerts
|

The effect of thyroid deficiency on the growth of the brain and on the deposition of brain phospholipids in foetal and new‐born rabbits

Abstract: It has been suggested that lack of thyroid hormone during foetal life contributes to the mal-development of the brains of cretinous infants. It has not been easy to get direct evidence for this view, not only because of the difficulty of obtaining brain tissue from cretins, but also because cretinism is hardly ever diagnosed before the infant is several weeks old. There is, however, some evidence that in cretinism due to congenital aplasia of the thyroid the brain is histologically abnormal at or near the time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

1967
1967
1986
1986

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 21 publications
1
11
0
Order By: Relevance
“…The principal route of photoproduct elimination is thought to be through the bile. Onishi et al (8) have reported finding a bilirubin photoproduct, which they called "unknown pigment," in the bile and urine of infants treated with phototherapy. We have used a high pressure liquid chromatographic method to quantitate the urinary excretion of bilirubin isomers in nine preterm infants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The principal route of photoproduct elimination is thought to be through the bile. Onishi et al (8) have reported finding a bilirubin photoproduct, which they called "unknown pigment," in the bile and urine of infants treated with phototherapy. We have used a high pressure liquid chromatographic method to quantitate the urinary excretion of bilirubin isomers in nine preterm infants.…”
Section: Discussionmentioning
confidence: 99%
“…Most biochemical events of physiologic significance in the brain, such as the synthesis of myelin lipids, occur postnatally (8). In the presence of a change in cardiac insulin receptor number, an absence of a change in brain insulin receptor characteristics signifies a difference in organ maturity or a different response by separate organs to the same stimulus.…”
Section: Discussionmentioning
confidence: 99%
“…Cuaron et al [10] demonstrated that mater nal PTU treatment for as long as 20 days (starting from day 10 of gestation) in the rabbit did not alter the phospholipid content of the fetal brains (days 23, 25, 27, 29, and 31 of gestation) [10]. Soon after birth, the control brain phospholipid content dramatically increased whereas the PTU-treated neo natal brains failed to show this same increase [10]. Most of the brain lipid deposition occurs in cell membranes and myelin [29].…”
Section: Discussionmentioning
confidence: 99%
“…4], However, excess insulin downregulated the insulin receptors on cultured fetal type II pneumocytes [5]. In vivo, insulin administration resulted in a downregulation of neonatal brain insulin receptors [6], Glucocorticoids increased the fetal lung insulin receptor sites [1], decreased the liver insulin receptor number [3], and did not alter the heart or brain insulin receptor character istics [7], Thyroxine (T4), on the other hand, has been demonstrated to decrease insulin receptors in the adult adipocytes [8] and decrease the insulin sensi tivity of these cells [9], Propylthiouracil (PTU)-induced hypothyroidism in the fetus decreases the lung and liver insulin receptors [1,3], Since thyrox ine regulates neonatal brain metabolism [10,11] and congenital hypothy roidism is a relatively frequent clinical occurrence [12], the effect ofhypoand hyperthyroidism on the development of fetal and neonatal brain insu lin receptors was investigated.…”
Section: Introductionmentioning
confidence: 99%
“…There is no evidence that thyroid hormone plays any part in the early organization of those centers mediating behavior but its presence is essential for proper development of cortical structure and function during a critical stage of development. 'The effects of thyroid deficiency in early life upon brain phospholipid composition [26] and mitochondria1 support of protein synthesis [44] have been emphasized. It is interesting to note that thyroxine may enhance central nervous system maturation before an effect is produced on overall body metabolic rate [104].…”
Section: Endocrine Injluences On Embryonic and Fetal Developmentmentioning
confidence: 99%